Learning to Navigate a New Financial Technology : Evidence from Payroll Accounts - Breza, Emily; Kanz, Martin; Klapper, Leora (World Bank, Washington, DC, 2020)
How do inexperienced consumers learn to use a new financial technology? This paper presents results from a field experiment that introduced payroll accounts in a population of largely unbanked factory workers in Bangladesh. In the experiment, workers in a treatment group received monthly wage payments into a bank or mobile money account while workers in a control group continued to receive wages in cash, with a subset also receiving an account without automatic wage payments. The results show that exposure to payroll accounts leads to increased account use and consumer learning. Those receiving accounts with automatic wage payments learn to use the account without assistance, begin to use a wider set of account features, and learn to avoid illicit fees, which are common in emerging markets for consumer finance. The treatments have real effects, leading to increased savings and improvements in the ability to cope with unanticipated economic shocks. An additional audit study provides suggestive evidence of market externalities from consumer learning: mobile money agents are less likely to overcharge inexperienced customers in areas with higher levels of payroll account adoption. This suggests potentially important equilibrium effects of introducing accounts at scale.